2019
DOI: 10.1136/bmjqs-2018-008924
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nursing home quality indicators and potentially preventable hospitalisation

Abstract: BackgroundHospitalisations are very common among nursing home residents and many of these are deemed inappropriate or preventable. Little is known about whether clinical care quality is related to hospitalisation, especially potentially preventable hospitalisations (PPHs). Among the few studies that have been conducted, the findings have been inconsistent. The objective of this study was to examine the relationship between quality indicators and overall and PPHs among Medicaid beneficiaries aged 65 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…One consistent message from the many studies that have examined nursing home quality is that our quality measures do not always measure what matters. In this issue of BMJ Quality & Safety , Xu and colleagues2 provide more evidence of the weak and unpredictable relationship between nursing home quality measures and an important patient outcome that does matter—hospitalisation. Using an expanded set of quality measures collected in Minnesota nursing homes, the authors find that the 23 metrics they examine showed neither strong nor consistent associations with risk of hospitalisation in a population of Medicaid residents—neither the overall rate of hospitalisation nor potentially preventable hospitalisations 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One consistent message from the many studies that have examined nursing home quality is that our quality measures do not always measure what matters. In this issue of BMJ Quality & Safety , Xu and colleagues2 provide more evidence of the weak and unpredictable relationship between nursing home quality measures and an important patient outcome that does matter—hospitalisation. Using an expanded set of quality measures collected in Minnesota nursing homes, the authors find that the 23 metrics they examine showed neither strong nor consistent associations with risk of hospitalisation in a population of Medicaid residents—neither the overall rate of hospitalisation nor potentially preventable hospitalisations 2.…”
mentioning
confidence: 99%
“…In this issue of BMJ Quality & Safety , Xu and colleagues2 provide more evidence of the weak and unpredictable relationship between nursing home quality measures and an important patient outcome that does matter—hospitalisation. Using an expanded set of quality measures collected in Minnesota nursing homes, the authors find that the 23 metrics they examine showed neither strong nor consistent associations with risk of hospitalisation in a population of Medicaid residents—neither the overall rate of hospitalisation nor potentially preventable hospitalisations 2. Further, while some associations were expected (eg, nursing homes with lower usage of urinary catheters had fewer hospitalisations for urinary tract infections), some were not.…”
mentioning
confidence: 99%
“…Both inappropriate-and under-prescribing increase mortality rates and hospital admissions [10]. Up to 92% of ADEs, adverse drug reactions (ADRs), and medicines' mismanagement (including patient safety incidents where patients and professionals contribute) are preventable [11][12][13][14]; more are due to poor monitoring than poor prescribing [15][16][17][18][19] and are dose-related [20,21]. Enhanced patient monitoring and/or reviewing would enhance efforts to ameliorate, if not resolve, the situation [9,16,17,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we continue to have major quality‐related concerns (Burke & Werner, 2019). In previous long‐term care studies, there have been numerous conceptualisations and measurements of care quality, and while some of the measures were associated with client outcomes, others were not (Werner, Konetzka, & Kim, 2013; Xu, Kane, & Arling, 2019). Burke and Werner (2019) called for further determination on the factors that should be measured; in other words, they stressed the importance of measuring what mattered and realistically affected patient outcomes.…”
Section: Introductionmentioning
confidence: 99%